The implementation of green construction in IKN development by integrating sustainable triangle concept into sustainable development goals - Yenita, Yenita; Soegiarso, Roesdiman (Frontiers in Political Science, 2024)
This study examines the integration of green construction in the development of Indonesia’s new capital city, Ibu Kota Nusantara (IKN), by applying the Sustainable Triangle Concept within the framework of Sustainable Development Goals (SDGs). The research addresses critical issues such as environmental sustainability, economic viability, and social inclusivity in developing IKN. Employing a quantitative descriptive approach, the study collected data through a purposive sampling method from 100 stakeholders, including environmental experts, community members, and contractors involved in IKN projects. Structural Equation Modeling (SEM) analysis, performed with PLS software, revealed significant relationships between green construction and sustainable development, with the environmental, economic, and social aspects serving as mediating variables. Findings indicate that green construction practices positively impact sustainable development by fostering energy efficiency, utilizing sustainable materials, and enhancing community welfare. The study highlights that sustainable urban development in IKN can serve as a model for balancing economic growth with environmental preservation and social equity, supporting Indonesia’s broader sustainability goals. This research contributes to theoretical and practical knowledge, offering a replicable model for policymakers and stakeholders seeking to implement sustainable practices in urban development. Future research is suggested to further explore the replicability of this model in other regions, addressing broader challenges and opportunities in sustainable urban planning.